Satchel Paige : striking out Jim Crow - Sturm, James, 1965- (Hyperion/Jump at the Sun, 2007)
A graphic novel account of the career of Negro League pitcher Satchel Paige, discussing the show he put on as a popular player, as well as the respect he demanded as an African-American.